Improving adversity quotient (AQ) with discovery learning - D D Frimadani; D B Widjajanti (Pascasarjana Universitas Pendidikan Indonesia, 2018)
Adversity Quotient (AQ) is one's ability to survive the difficulty and manage the adversity until it finds the way of its predicament. A person with a good AQ ability can achieve goals by facing difficulties. The role of AQ is important in mathematics learning. The researcher observed the students' AQ, got the student’s average in the medium level. This study uses AQ with stimulation, problem statement, data collection, data processing, verification, and generalization. The purpose of this study is to increase adversity quotient in junior high school eighth-grade student of SMP Muhammadiyah 2 Depok, Yogyakarta. This research was conducted on the mathematics lesson of The Linear Equation System (SPLDV) in the odd semester academic year 2017/20018. This research is a classroom action research using two cycles, each cycle consists of three steps which are conducted in two meetings by using discovery learning. Instruments performed in this study are questionnaires AQ, lesson plan, and student worksheet. After learning with discovery learning, students can increase AQ in each cycle. The student’s average has a high AQ. The results of this study indicate that the learning scenario that designed in each cycle can improve the adversity quotient students.